2016
DOI: 10.1021/acs.jpca.6b00036
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Vibrationally Averaged Nuclear Shielding Constants by Quantum Diffusion Monte Carlo and Second-Order Perturbation Theory

Abstract: Using the method of modified Shepard's interpolation to construct potential energy surfaces of the H2O, O3, and HCOOH molecules, we compute vibrationally averaged isotropic nuclear shielding constants ⟨σ⟩ of the three molecules via quantum diffusion Monte Carlo (QDMC). The QDMC results are compared to that of second-order perturbation theory (PT), to see if second-order PT is adequate for obtaining accurate values of nuclear shielding constants of molecules with large amplitude motions. ⟨σ⟩ computed by the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…[23][24][25][26][27] For the case of the zero-point vibrational effects, we have shown that, for molecules with large amplitude motions, the most accurate of ZPVCs can only be obtained with the use of more sophisticated and accurate methods, such as quantum diffusion Monte Carlo. [28] Nevertheless, second-order perturbation theory [23] remains as the most widely used approach for calculating vibrational contributions to NMR properties. This is mainly due to the cost effectiveness of the method, making it particularly scalable to the study of larger systems.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] For the case of the zero-point vibrational effects, we have shown that, for molecules with large amplitude motions, the most accurate of ZPVCs can only be obtained with the use of more sophisticated and accurate methods, such as quantum diffusion Monte Carlo. [28] Nevertheless, second-order perturbation theory [23] remains as the most widely used approach for calculating vibrational contributions to NMR properties. This is mainly due to the cost effectiveness of the method, making it particularly scalable to the study of larger systems.…”
Section: Introductionmentioning
confidence: 99%